The Impact of Hybrid Work Models on Employee Engagement in IT Sector in the Czech Republic - Razin, Mykyta; Hořáková, Marie; Legnerová, Kateřina, 1965-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The aim of this bachelor’s thesis is to explore how hybrid work models influence employee engagement and motivation within the IT sector in the Czech Republic. The theoretical section provides an overview of the development of hybrid work, key models, and factors affecting employee engagement, including motivation, communication, and job satisfaction. The research applies a mixed-method approach, combining qualitative interviews with managers from two IT companies and a quantitative survey distributed among employees working in hybrid roles. The methodology is designed to capture both managerial perspectives and employee experiences. The thesis focuses on examining the relationship between hybrid work arrangements and employee engagement in the context of the Czech IT industry.
Vedoucí práce: Marie Hořáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses